A Quasi-Experimental Study On The Impact Of The Picture Word Inductive Model On The Vocabulary Acquisition Of Year 1 Learners In Malaysia - Lee, Bee Choo (2013)
Given the significance of vocabulary knowledge to language development (Cunningham & Stanovich, 1997; Hazenberg & Hulstijn, 1996; Nation, 1990), this study examined how pictures impact vocabulary acquisition of a group of Year 1 students in Malaysia through the Picture Word Inductive Model (PWIM). The experimental group of this study consisted of 32 Year 1 students from a Malaysian public primary school, while the control group also consisted of 32 Year 1 students, from another primary school in the surrounding area. The study also compared vocabulary recall and retention of the two study groups. The PWIM, designed by Calhoun (1999), employs pictures to elicit words from students’ existing listening and speaking vocabularies. The developer has used the PWIM successfully and extensively with learners of various levels and ability levels in her own country and some other countries as well. Data collected from pretests, posttests, and delayed posttests were analysed and assessed for statistically significant differences between the experimental and the control group. The findings suggest that although both study groups recorded positive results in the vocabulary tests, those who experienced the PWIM intervention achieved a more significant increase in their vocabulary recall and retention as compared to those in the control group who were taught via typical classroom instruction. This indicates that the PWIM appears to be a more effective instructional tool in facilitating vocabulary acquisition.